APPLICATION OF ANALYTIC NETWORK PROCESS (ANP) METHOD BASED ON ESTABLISHED CRITERIA IN THE SELECTION OF THE LOCATION OF MAKO LANTAMAL VI - Rudi Hartono Siregar; Adi Bandono; Ahmad Sumarton; Atiq Alfiansyah (Indonesian Naval Technology College STTAL, 2024)
This study discusses the degradation condition of the Makassar VI Naval Base which has experienced a decline in its function as an operational support center for the Indonesian Navy. So that it has an impact on the optimality of the implementation of base duties. Through the application of the Analytic Network Process (ANP) method, this study aims to determine the best alternative in choosing the location of Mako Lantamal VI. The alternative involves Lanal Mamuju, Lanal Kendari, Lanal Baubau, and Lanal Palu which are work units under Lantamal VI Makassar which are located in the Sea Route of the Islands II (ALKI II). Criteria and subcriteria in determining the best alternative include, geography, resources, and socio-cultural aspects. As a result, this research is expected to be a strategic foundation in preparing a plan for projecting the strength of the Indonesian Navy in the future. Where is the urgency in this research, so that the function of the base according to its principles can still be carried out. This study intends to select the location of Mako Lantamal VI due to the degradation of the base function which results in the main functions and tasks of the base being constrained, The solution of this study will use the Analytical Network Process (ANP) method where the results of data processing are obtained by the weight of geography criteria (0.47433), socio-cultural (0.13536), and resource criteria (0.237890).